2017
DOI: 10.1016/j.indcrop.2017.09.046
|View full text |Cite
|
Sign up to set email alerts
|

Residual contact toxicity and repellence of Cupressus lusitanica Miller and Eucalyptus saligna Smith essential oils against major stored product insect pests

Abstract: In an effort to find eco-friendly alternatives to synthetic pesticides in grain storage, residual contact toxicity and repellence of Cupressus lusitanica and Eucalyptus saligna leaf essential oils were evaluated against adult Tribolium castaneum, Acanthoscelides obtectus and Sitophilus zeamais. In bioassays, oil was applied at 0.00, 0.05, 0.10, 0.15 and 0.20% v/w to wheat and bean grains and stored for 30-120 days after which test insects were introduced into sub-samples of treated grains. Both oils at 0.20% v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 33 publications
1
25
1
1
Order By: Relevance
“…α‐Pinene, β‐pinene, β‐caryophyllene, and manool are the major constituents of several Pinus species [43] . α‐Pinene, 13‐epi‐manoyl oxide and β‐caryophyllene are reported in Eucalyptus species [44] . The monoterpenes α‐pinene and β‐pinene were identified in Araucaria angustifolia , the representative specie of the Araucariaceae in Brazil [45] …”
Section: Resultsmentioning
confidence: 99%
“…α‐Pinene, β‐pinene, β‐caryophyllene, and manool are the major constituents of several Pinus species [43] . α‐Pinene, 13‐epi‐manoyl oxide and β‐caryophyllene are reported in Eucalyptus species [44] . The monoterpenes α‐pinene and β‐pinene were identified in Araucaria angustifolia , the representative specie of the Araucariaceae in Brazil [45] …”
Section: Resultsmentioning
confidence: 99%
“…Previous studies of EO effects in A. obtectus have involved EOs isolated from plants belonging to families of Amaranthaceae [58], Asteraceae [59], Cupressaceae [60], Lamiaceae [61][62][63], Lauraceae [64], Meliaceae [65], Myrtaceae [60,62,64,66], Piperaceae [65], Poaceae [67], Rutaceae [68]. In the present study we examined how thyme EO (Thymus vulgaris L., Lamiaceae, thymol chemotype) applied by contact affected A. obtectus mortality, F1 progeny production and choice of seeds for oviposition.…”
Section: Introductionmentioning
confidence: 99%
“…However, the amount concentrations of components vary from one region to another due to the influence of many factors, including harvest season, climate, soil type, age of the plants and the extraction . For example, Bett et al [58] reported the dominance of oxygenated monoterpenes in the leaf EOs of C. lusitanica growing in Kenya with umbellulone (18.38%), αpinene (9.97%), sabinene (8.16%) and limonene (7.91%) as major compounds. Almost similar results were reported by Kuiate et al [20] for leaves in Cameroon with dominance of umbellulone (18.30%), pinene (7.40%), epizonarene (5.0%), limonene (3.5%) and terpinenol (2.6%).…”
Section: Gc-ms Results Of Essential Oil From C Lusitanica Leavesmentioning
confidence: 99%